2010
DOI: 10.1111/j.1439-0396.2009.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rumen-protected choline and methionine on physiological and metabolic disorders and reproductive indices of dairy cows

Abstract: The objective of this study was to investigate the effect of feeding different levels of ruminally protected methionine and choline on the incidence of physiological and metabolic disorders, production, and some of the reproductive indices of Holstein dairy cows. Forty Holstein dairy cows in their first and second lactation were used from 4-week pre-partum through 20-week post-partum and randomly assigned to receive one of the following treatments: 18 g/day of rumen-protected methionine (RPM), 60 g/day of rume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…In this sense, methionine supplementation before and around conception seems to be a promising tool for improving reproductive performance in lactating dairy cattle [18]. Previous studies in ruminants have indicated that a methionine-deficient diet provided to the dam prior to and for the first six days after conception can produce substantial changes in the offspring such as elevated blood pressure, insulin resistance, and altered immune response [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, methionine supplementation before and around conception seems to be a promising tool for improving reproductive performance in lactating dairy cattle [18]. Previous studies in ruminants have indicated that a methionine-deficient diet provided to the dam prior to and for the first six days after conception can produce substantial changes in the offspring such as elevated blood pressure, insulin resistance, and altered immune response [19].…”
Section: Introductionmentioning
confidence: 99%
“…Rumen-protected choline (RPC) supplementation to both transition and early lactating dairy cows, usually provided as choline chloride coated with hydrogenated oils (Pinotti et al, 2002), has been demonstrated to improve milk production (Erdman and Sharma, 1991;Pinotti et al, 2003;Ardalan et al, 2010) and the metabolism of lipids and methyl groups (Piepenbrink and Overton, 2003;Baldi and Pinotti, 2006). Moreover, supplemental choline may improve the transport of lipids in the blood, thus reducing the risk of fatty liver disease and ketosis in periparturient dairy cows, as choline is an essential component of the phospholipids that are at the core of the structure of lipoproteins (Pinotti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing RPM to the diet of dairy goats increased ECM (Flores et al 2009). Moreover, Ardalan et al (2010) and Soltan et al (2012) suggest that the increased ECM suggests that RPM can positively impact milk energy output when early-lactation curve peaks and drops. No effect of RPM supplementation was reported on ECM of dairy cows (Girard et al 2005).…”
Section: Milk Yield and Compositionmentioning
confidence: 99%